Pregnancy and Perinatal Care Experiences of First Nations Women in a Urban Context - Tremblay, Justine; Leclerc, Anne-Marie; Lemieux, Roxanne; Cleary, Jessica; Weizineau, Eden; Berthelot, Nicolas (Science of Nursing and Health Practices, 2024)
Introduction: During pregnancy, many First Nations women must travel to urban areas for perinatal care. Accessibility issues and the presence of certain risk factors (e.g., gestational diabetes) are omnipresent. Mistrust of health care and social services may increase their vulnerability during this period. Objectives: To describe the perinatal experience of First Nations women, their assessment of care received and how they would like to be accompanied by health professionals during this period. Method: A descriptive phenomenological study was conducted with 10 First Nations women transiting to urban areas for care. Individual interviews were analyzed using Giorgi's method (1997). Results: For participants in this study, pregnancy is a positive and holistic experience which all dimensions of health are influenced — physical, psychological, emotional and spiritual. In terms of care, trust is paramount. However, most participants reported negative experiences during their perinatal care (e.g., reactivation of traumas). Finally, in terms of expectations, they would like to receive more information and a sense of acknowledgment of their culture during this perinatal period. Discussion and conclusion: For the participants, motherhood gave them the opportunity to prove their resilience. The use of positive levers promotes the well-being of First Nations women. It is essential to include the realities and cultural particularities of First Nations women in the approaches to care provided by health professionals during this important period. Introduction : Pendant leur grossesse, plusieurs femmes des Premières Nations doivent transiter en milieu urbain pour obtenir des soins périnataux. Les enjeux d’accessibilité et la présence de certains facteurs de risque (ex., diabète gestationnel) sont omniprésents. Or, la méfiance qu’elles entretiennent face aux soins de santé et aux services sociaux pourrait contribuer à accroître leur vulnérabilité lors de cette période. Objectifs : Décrire l’expérience périnatale de femmes ...